2011
DOI: 10.1055/s-0031-1280219
|View full text |Cite
|
Sign up to set email alerts
|

ZYM-201 Sodium Succinate Ameliorates Streptozotocin-Induced Hyperlipidemic Conditions

Abstract: ZYM-201 is a methyl ester of a novel triterpenoid glycoside. It is isolated from SANGUISORBA OFFICINALIS, a widely used medicinal plant in Korea, China, and Japan, that is prescribed for various diseases such as diarrhea, chronic intestinal infections, duodenal ulcers, and bleeding. In this study, the antihyperlipidemic effect of the salt form (sodium succinate) of ZYM-201 was examined using streptozotocin (STZ)-treated hyperglycemic rats. Oral administration of ZYM-201 sodium succinate (3 to 10 mg/kg) resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Since we found that DWP208, a water-soluble salt form of ZYM-201, is able to normalize the up-regulated levels of hyperlipidemic parameters in an animal model of streptozotocin-induced diabetes that was simultaneously fed a high fat diet [ 20 ], we examined the effects of DWP208 on alcohol-induced hyperlipidemia. Chronic alcohol addiction is more prevalent in the Korean population and causes serious effects such as liver damage, leading to the generation of fatty liver, cirrhosis, and liver cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we found that DWP208, a water-soluble salt form of ZYM-201, is able to normalize the up-regulated levels of hyperlipidemic parameters in an animal model of streptozotocin-induced diabetes that was simultaneously fed a high fat diet [ 20 ], we examined the effects of DWP208 on alcohol-induced hyperlipidemia. Chronic alcohol addiction is more prevalent in the Korean population and causes serious effects such as liver damage, leading to the generation of fatty liver, cirrhosis, and liver cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Also, DWP208 was able to ameliorate the hyperlipidemia induced by a high fat diet or streptozotocin [ 20 ]. Furthermore, DWP208 protected against the hyperlipidemia induced by chronic alcohol intake.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these results point towards the additional utility of OPF as an antihypertriglyceridimic and anti-hyperlipedemic agent. A recent study reported an antidiabetes compound sodium succinate capable of ameliorating such diabetes derived hyperlipidemic complications (Choi et al, 2012). In diabetic subjects, the body weight tends to reduce significantly as a result of extreme protein catabolism leading to muscle wasting.…”
Section: Groupsmentioning
confidence: 99%
“…Taken together, these data indicate that ZYM-201, which has been known to have inhibiting tissue factor activity, TNF-α production and modulating hyperlipidemic conditions ( 10 , 11 , 12 ), has another function of anti-inflammatory activities via inhibition of NF-κB activation and downregulation of costimulatory molecules in B cells. In agreement with this, previous studies showed that inhibition of NF-κB activation suppress inflammatory responses ( 23 ) and have anti-inflammation and anticancer effects ( 24 ), and suggested that it could be used to treat immune diseases ( 25 ).…”
Section: Resultsmentioning
confidence: 67%
“…ZYM-201 is a modified compound of ziyuglycoside, one of triterpene glycoside originated from the root of S. officinalis , through deglycosidation and esterification ( 10 ). Previous studies have shown that ZYM-201 plays a role in inhibiting tissue factor activity, tumor necrosis factor (TNF)-α production and modulating hyperlipidemic conditions ( 10 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%